Evaluating Cross-Border E-CommerceDevelopment and Trade Potential Between China and RCEP Countries : An Ecosystem-Based Gravity Model Approach - Lili, Zhang; Muhammad Asraf, Abdullah; Min, Huang; Lihong, Dai (Human Resource Management Academic Research Society (HRMARS), 2025)
This study explores the development level and trade potential of cross-border e-commerce (CBEC) between China and its Regional Comprehensive Economic Partnership (RCEP) partners. Based on the CBEC ecosystem theory, a composite development index is constructed using Principal Component Analysis (PCA), incorporating key variables such as logistics performance, information flow, and digital infrastructure. An extended gravity model, estimated through the Generalized Method of Moments (GMM), is applied to panel data covering the period from 2013 to 2022. The empirical results underscore the crucial role of logistics and information flow in promoting CBEC growth across the region. China maintains a leading position due to its superior infrastructure, while countries like Laos remain constrained by infrastructural and economic limitations. The study finds that CBEC development in partner countries significantly enhances their trade with China, whereas China’s own CBEC level has a limited effect on overall trade volumes. Additionally, while partner countries’ per capita GDP does not exhibit a significant influence, China’s per capita GDP positively affects trade flows, and geographic distance has a weak but statistically significant negative impact. The analysis also reveals untapped CBEC trade potential in countries such as Japan and South Korea, indicating the need for targeted policy interventions to strengthen digital infrastructure, reduce trade frictions, and foster deeper e-commerce integration within the RCEP framework.